Compound Words in Evermore Album by Taylor Swift: A Morphology Study - Nabila Rachman; Ervina CM Simatupang (Universitas Cokroaminoto Palopo, 2022)
The aims of this study are (1) to explain the types of compound words and (2) to explain the meanings of compound word found in the ninth studio album titled “evermore” by Taylor Swift. The method for this research was conducted using a descriptive analytic method with the theory from Sugiyono (2010). In analyzing the data, this analysis used the theory of compound words with compounding method of Delahunty and Garvey’s statement (2010), and Falk’s (1978: 43). The data used were taken from the international music platform named Apple Music. This research shows that there are 35 data of compound word found in the ninth studio album titled “evermore” by Taylor Swift. The results demonstrated that there are three types of compound word found, namely 26 (74%) of compound nouns, 1 (2,8%) of compound verbs, and 8 (22%) of compound adjectives. The finding of this research is that compound nouns are the most common types of compound words that appear in this album with a percentage of 74%, while the compound verbs show with a percentage of 1,8% and compound adjective show with a percentage of 22%.